DETERMINASI EFISIENSI TEKNIS PENGGUNAAN FAKTOR PRODUKSI PADA USAHATANI PADI LAHAN IRIGASI KABUPATEN LOMBOK BARAT - HERNAWATI, HERNAWATI; SUDANTHA, I MADE ANGGAYUDA PRAMADYA (Universitas Mahasaraswati Mataram, 2018)
This study aims to find out: 1). procedures for using production factors, 2). production factors that significantly influence the level of production in rice farming, 3). level of technical efficiency in the use of production factors, 4). determinants of the level of technical efficiency, 5). the amount of expenditure and income earned by farmers from rice farming on irrigated land in West Lombok Regency. The analysis used in this study is descriptive analysis, multiple linear regression analysis with Cobb Douglass function and frontier analysis.The results show that 1) irrigated rice cultivation is carried out in MH and ICM, with a monoculture planting system. There is a waste in the use of seeds because the use is more than a recommendation, the dominant variety is Invari 32. Then at the stage of land processing and planting the biggest use of labor was 40 HKO. The use of fertilizer was not balanced and not exactly dose 2). Production factors that significantly affect the level of production in rice farming in irrigated land are land area, seeds, fertilizer (Urea + SP36) and pesticides 3). The average level of technical efficiency achieved is 0.899 (89.9%), meaning that the average productivity achieved is around 90 percent 4). Factors that significantly influence the level of efficiency in the use of production factors are the number of parcels, farming experience, education of the household head and the frequency of planting in one year because the t-count value is greater than t-table 1.96. 5). The income that farmers receive from their rice farming is Rp. 9. 278,200, - / hectare with production costs that must be spent on average per hectare of Rp. 8,081,800, - Therefore rice farming in irrigated land is economically beneficial because of the value of its business efficiency (R / C) 1.15.Keywords: Determination, efficiency, production factors, farming, rice